Asian Values and Influence on Bureaucracy: Toward World Class Governance - Yosafat, Yosafat (Iapa Proceedings Conference, 2024)
This research paper explores the impact of Asian values on bureaucratic governance, aiming to achieve world-class standards. The concept generally refers to a set of cultural, social, and political beliefs that are considered characteristic of societies in East Asia and Southeast Asia. It investigates how Asian values are believed to shape cultural norms, ethical principles, and traditional philosophies that influence bureaucratic structures and practices. Drawing on diverse perspectives across Asia, the study examines how values like collectivism, respect for authority, social harmony, and strong work ethic shape administrative processes and decision making. Using an interdisciplinary approach, this research analyzes the implications of Asian values for transparency, accountability, and efficiency within bureaucratic systems. Case studies and comparative examples are employed to illustrate the strengths and challenges of integrating Asian values into global governance models. Additionally, the research explores how traditional Asian values intersect with modern bureaucratic principles, identifying areas of alignment and divergence. By synthesizing insights from cultural studies, political science, and public administration, this paper offers a nuanced understanding of the complex relationship between Asian values and bureaucratic governance. It underscores the importance of recognizing cultural diversity in pursuing world-class standards and advocates for inclusive approaches that honor Asian heritage while striving for excellence in global governance practices.